2016
DOI: 10.1177/1933719115602763
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of WNT4 in Ectopic and Eutopic Endometrium of Human Endometriosis

Abstract: The objective was to investigate the expression of the WNT4 gene in ectopic endometrium and eutopic endometrium (EU) during endometriosis and the relationship of WNT4 expression with the menstrual cycle. Ectopic endometrium and EU tissues were collected from 30 women with pathologically confirmed endometriosis and 30 women without endometriosis. The WNT4 protein and messenger RNA (mRNA) expression levels were measured by fluorescence-based quantitative real-time polymerase chain reaction, immunohistochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Interestingly, the proliferation of eutopic endometrial MSCs was elevated by endometriotic PF much remarkably than ectopic endometrial MSCs derived from the same patients, while the proliferation of normal endometrial MSCs was inhibited in the same condition. These data suggest that there are some inherent differences between endometrial MSCs from patients with and without endometriosis facilitating the proliferation of eutopic but not normal endometrial MSCs in the presence of endometriotic PF, which is consistent with the theory of “eutopic endometrium determinism” [44].…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the proliferation of eutopic endometrial MSCs was elevated by endometriotic PF much remarkably than ectopic endometrial MSCs derived from the same patients, while the proliferation of normal endometrial MSCs was inhibited in the same condition. These data suggest that there are some inherent differences between endometrial MSCs from patients with and without endometriosis facilitating the proliferation of eutopic but not normal endometrial MSCs in the presence of endometriotic PF, which is consistent with the theory of “eutopic endometrium determinism” [44].…”
Section: Discussionsupporting
confidence: 86%
“…In a histological comparison of IHH expression in endometrial biopsy samples from women with endometriosis and healthy controls, IHH expression was decreased in secretory phase endometrium from endometriosis patients [155]. Correspondingly, later studies found COUPTFII [131] and WNT4 [132] expression levels decreased in both endometrial samples from women with endometriosis and endometriotic lesions. These findings identified a major pathway downstream of P4 signaling that is disrupted in women with endometriosis and may lead to endometrial non-receptivity in these patients by interfering with regulation of uterine epithelial proliferation and stromal decidualization.…”
Section: Dysregulation Of Progesterone and Estrogen Signaling In Ementioning
confidence: 99%
“…Several other steroid hormone-regulated pathways we have discussed are both implicated in endometriosis and closely involved in pregnancy establishment. Proteins involved in regulation and mediation of the P4-responsive IHH pathway including GATA2, SOX17, IHH, COUPTFII, and WNT4 are required for successful implantation in mice [29,30,34,65,67] but are reduced in the endometrium of women with endometriosis [68,131,132,136,155], revealing a potential large-scale molecular connection between P4 resistance and fertility problems in endometriosis. The transcriptional regulators FOXO1, ARID1A, and HDAC3 are three additional factors associated with P4 signaling that are required for uterine receptivity in mice and down-regulated in the endometrium of women with endometriosis, further corroborating the association between the P4 resistance of endometriosis with infertility [55,69,119,144,157].…”
Section: Pathologies Related To Steroid Hormone Signaling Dysregulmentioning
confidence: 99%
“…The Wnt family protein Wnt-4 is essential for the development of the female reproductive tract (Vainio et al 1999), and acts as a signalling molecule in cell-cell interactions, proliferation and migration (Liang et al 2016). Expression levels of WNT4 in the eutopic endometrium appear to be higher in a group of women with endometriosis than in a control group (Liang et al 2016). Moreover, a GWAS found that a SNP located close to the WNT4 gene (rs7521902) was associated with the endometriosis risk (Pagliardini et al 2013).…”
mentioning
confidence: 99%